TOMM40L promotes proliferation and migration of triple negative breast cancer cells and correlates with poor prognosis - ZHANG Ke, LU Jiangning, SUN Lixin, YU Long, SUN Lichao, RAN Yuliang (Jichu yixue yu linchuang)
Objective To explore the clinical significance and to investigate the expression of TOMM40L in the tissue of triple-negative breast cancer (TNBC). Methods The expression of TOMM40L in TNBC tissues and normal tissues was analyzed with TCGA and UALCAN databases. Univariate and multivariate Cox regression analysis and Nomogram model were used to evaluate the prognostic value of TOMM40L in TNBC patients. Furthermore, the expression of TOMM40L in breast cancer cell lines was evaluated using Western blot analysis and quantitative real-time PCR. Specific siRNA knockdown was performed to evaluate the migration, and cell proliferation of TOMM40L. The potential signaling pathways of TOMM40L were identified by GO and KEGG and GSEA. Results TOMM40L was highly expressed in the TNBC compared to non-TNBC tumor tissues(P＜0.001). TOMM40L levels were enhanced in TNBC cell lines as compared to other non-TNBC cell lines. CCK-8 and Transwell assay demonstrated that TOMM40L knockdown reduced the proliferation and migration of TNBCcell lines. Functional enrichment analysis showed that TOMM40L was involved in glucose metabolism-related pathways. Conclusions The expression of TOMM40L is increased in TNBC and is correlated with poor prognosis. TOMM40L may promote TNBC migration and proliferation.